Expanding Legal Migration Pathways from Nigeria to Europe : From Brain Drain to Brain Gain - Adhikari, Samik (World Bank and Center for Global Development, Washington, DC, 2021)
The world is currently at a crossroads. Low- and middle-income countries such as Nigeria are seeing rapid growth in their working-age populations. Yet often, these increasingly educated and skilled young people cannot find meaningful work within their countries of origin, either because their skills are not well aligned to the needs of employers or because there is an absolute lack of roles available. This is creating emigration pressure, with many seeking opportunities elsewhere, leading to fears of brain drain within countries of origin. At the same time, high-income countries such as those in Europe are seeing rapid decreases in their working-age populations. Employers within these countries are facing significant skill shortages, which is reducing productivity and investment. Based on interviews with more than 100 stakeholders, this report applies the center for global development’s (CGD) global skill partnership model to the sectors of health care, construction, and information and communications technology (ICT), designing partnerships between Nigeria and select countries of destination in Europe. It outlines how countries of destination looking to fill labor shortages can provide high-quality and industry-relevant training to potential migrants and nonimmigrants within Nigeria, increasing the global stock of workers and contributing to brain gain.